Preparation, Characterization And Application Of Magnesium Salt-Polyacrylamide Hybrid Materials In Dye Wastewater Treatment - Lee, Khai Ern (2012)
Magnesium salt-polyacrylamide hybrid materials were prepared, characterized and applied for reactive dye wastewater treatment. Polyacrylamide was prepared from acrylamide monomer through redox polymerization. The fundamental aspects of polyacrylamide redox polymerization were studied through investigation of mechanism, kinetics, thermodynamics and in situ rheological properties of the redox polymerization process. The redox polymerization of polyacrylamide was optimized through design of experiment. The physicochemical properties of the polyacrylamide were investigated in terms of chemical structure, molecular weight distribution as well as viscosity in aqueous solution. The yield of the optimal redox polymerization of polyacrylamide was 96.89% with molecular weight of 1.66 x 106 Da. Magnesium salt-polyacrylamide hybrid materials were prepared through physical blending of magnesium chloride and magnesium hydroxide with polyacrylamide in aqueous solution to form magnesium chloride-polyacrylamide (MCPAM) and magnesium hydroxide-polyacrylamide (MHPAM) hybrid materials, respectively.